The Influence of Perceived Ease of Use, Perceived Benefits, and Trust on the Intention to Use Dana E-Wallet Among Users in Indonesia - Berliana Agustin; Dora Rinova (Cita konsultindo, 2024)
This research focuses on E-wallet Dana users found in Indonesia. It employs a quantitative research method to investigate various perceptions such as perceived ease, benefits, and trust, and their significant positive influence on the interest in using E-wallet Dana in Indonesia. The research utilizes a questionnaire as a data collection technique with SPSS 29. The population of this study is 150 million E-wallet Dana users in Indonesia, with a sample size of 100 respondents. The research involves various tests including instrument testing, classic assumption testing, multiple regression testing, and hypothesis testing. Partially, the findings indicate that perceived ease does not significantly influence the interest in using E-wallet Dana, whereas perceived benefits and trust have a significant impact on the usage intention of E-wallet Dana. Simultaneously, perceived ease, perceived benefits, and trust collectively exert a significant influence on the interest in using E-wallet Dana.